Total keratometry for toric intraocular lens calculation: comparison from two swept-source optical coherence tomography biometers - Chai, Feiyan; Ma, Jack X.; Wang, Xiaogang; Liu, Jiewei; Jiang, Lin; Wu, Wanmin; Li, Junhong (Frontiers in Medicine, 2024)
Purpose To compare the astigmatism prediction accuracy of total keratometry (TK) from the IOLMaster 700 and total corneal power (TCP) from Anterion based on swept-source optical coherence tomography (SS-OCT) technology in toric intraocular lens (toric IOL) calculation. Design A retrospective observational study. Methods Total corneal astigmatism (TCA) were obtained using IOLMaster 700 and Anterion. Z CALC 2.0 was used to calculate the expected postoperative refractive astigmatism in conjunction with TCA. Prediction errors (PE) in refractive outcomes was analyzed 1 month postoperatively using the vector analysis by the Holladay method, including the mean vector PE magnitude, percentage of cases with vector PE in certain intervals, and the centroid PE. Results A total of 56 eyes from 56 patients were enrolled in the study with an insertion of an AT TORBI 709 toric IOL. The difference in mean vector PE of postoperative refractive astigmatism between TK and TCP was not statistically significant (0.48D versus 0.46D, P = 0.281). TK and TCP yielded 27.3 and 40.0% of eyes with vector PE ≤ 0.25D, and 58.2 and 63.6% with vector PE ≤ 0.5D (both P > 0.05), respectively. TK and TCP resulted in similar ATR centroid PE of 0.10D@35° ± 0.60D and 0.15D@22° ± 0.57D, respectively, and there were no significant differences between x-PE component and y-PE component. Conclusion IOLMaster 700 and Anterion provided comparable astigmatic predictability in toric IOL implantation using total keratometry and Z CALC 2.0.